International Trade Regulations on BPA: Global Health and Economic Implications - Kadasala, Naveen Reddy; Narayanan, Badri; Liu, Yang (Asian Development Policy Review, 2016)
Several international trade agreements being negotiated today are mostly aimed at enhancing trade and economy, with less or no concern about other important aspects, including environment. However, there have been some trade regulations as well as rules within some of these agreements that aim at enforcing stringent requirements and constraints on free trade of certain commodities that harm the environment and increase risk factors of diseases. Bisphenol A (BPA) is one such commodity and is the focus of this paper. Despite its heavy use across the world, BPA has severe health and ecological effects, leading the developed countries to impose regulations on them. This paper reviews the adverse health and ecological effects of BPA as well as the regulations on them. It further goes on to perform an economic model simulation using a widely used global model named GTAP, to understand the global economic effects of banning the trade of BPA. We also estimate the costs arising from the adverse health effects of BPA using WHO-DALY dataset and the literature. We arrive at a range of costs associated with health and conclude that regulating BPA is at best, a very inexpensive policy to promote health and economies of the world, and at worst, slightly more expensive than the health costs associated with BPA.